مسلمانوں کی طبی خدمات اور عصری معنویت تحقیقی جائزہ: Muslim Medical Services and Contemporary Meaning Research Review - Haroon, Muhammad; Dr Muhammad Waris Ali (MEI, 2023)
Where Islam has described teachings for the inner training of man, there are also instructions for his health and well being in Islamic teachings. That is why, when a disease is contracted, it has attracted towards treatment. There is a consistent body of Islamic teachings to protect the human body. Objectives There are guiding principles for the protection of the human body and human life in the Shari'ah. In the first period of Islam, medical guidance was found in the language of Prophethood. Then this field continued to develop in the era of the Prophet PBUH. This article is on "Medical services of Muslims in the era of the Prophet PBUH, a research review", in which the developments in the medical field in the era of the Prophet PBUH are mentioned. Initially, the literal meaning of the word medicine and its types are described. Along with this, the Quranic verses on medicine are also described. In modern times, where new diseases have affected the human body, the increasing number of Pathologists in different fields have fulfilled this need. Therefore, what were the medical services of Muslims in the era of the Prophet PBUH, in this article has been brought.